2010
DOI: 10.18097/pbmc20105602283
|View full text |Cite
|
Sign up to set email alerts
|

Activity of enzymes of a sphingomyelin cycle and concentration of products of sphingomyelin degradation in the liver of rats in dynamics of the acute toxic hepatitis

Abstract: Кафедра биохимии и молекулярной биологии ГОУ ВПО "Сибирский государственный медицинский университет Росздрава", 634050, г. Томск, ул. Московский тракт, 2; тел.: 8-(3822)-42-09-61; эл. почта: serebrov@ssmu.ru, dik51@mail.ru В печени крыс, изучали активность ключевых ферментов сфингомиелинового цикла и содержание его компонентов (сфингомиелина, церамида и сфингозин-1-фосфата) в динамике острого токсического гепатита, вызванного подкожным введением масляного раствора тетрахлорметана. Активность сфингомиелиназы до… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…PC participated in the repair of cell membranes and promoted the generation of choline to synthesize GSH acting as antioxidant, so PC showed the downtrend and its degradation products showed the same trend. Some studies have found that FA is the major energy resource under pressure [58]. It could provide energy for hepatocyte to facilitate its function by β -oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…PC participated in the repair of cell membranes and promoted the generation of choline to synthesize GSH acting as antioxidant, so PC showed the downtrend and its degradation products showed the same trend. Some studies have found that FA is the major energy resource under pressure [58]. It could provide energy for hepatocyte to facilitate its function by β -oxidation.…”
Section: Discussionmentioning
confidence: 99%